Motor function, community reintegration and quality of life in stroke survivors with pre-stroke driving history (2018)
Background: Driving is an important activity of daily living associated with improved community reintegration and better quality of life. It is however unclear if there is a definite difference in the motor function, community reintegration and quality of life of stroke survivors who returned to driving and those who did not. Methods: Stroke survivors with pre-stroke driving history participated in this cross sectional survey. Socio-demographics, clinical characteristics and driving history were documented. Motor function, community reintegration and quality of life were assessed using the Modified Motor Assessment Scale (MMAS), Reintegration to Normal Living Index (RNLI) and Health-Related Quality of Life in Stroke Patients (HRQOLISP-40) respectively. Returners and non-returners were compared using Mann Whitney U test at á0.05 . Results: Fifteen out of the 44 stroke survivors (34.1%) who participated in this study had returned to driving after their stroke. There was no significant difference in age, time since stroke onset and years of driving experience prior to stroke onset (p >0.05) between returners and non-returners. There was however a significant difference in the motor function, community reintegration and quality of life between the two groups (p<0.01) Conclusion: Stroke survivors with pre-stroke driving who returned to driving after stroke had better motor function, community reintegration and quality of life compared to their counterparts who had not returned to driving.